If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4z=7z=
We move all terms to the left:
4z-(7z)=0
We add all the numbers together, and all the variables
-3z=0
z=0/-3
z=0
| 24(3x-1)=28(x+7) | | -1+k=4.2 | | -6.1+2.5z=-4.4 | | 8(1-K)=3(k+12) | | 5x+3=5×-7 | | 4(3+5x)-2(x+1)=-62 | | u/11=-11 | | -3k=9.6 | | x²+20x-3149=0 | | 8q−5=9q−3 | | 1=u10-1 | | 11n-8≥=69 | | 8s2+14s=15 | | x⅔+20x-3149=0 | | -6x+4=6x-4 | | 27x+1+125=180 | | 2(6+5n)-3n=11+7n | | -7p-15=-2p;-3 | | (k+8.5/5.9)+15=-2.6 | | n/12=-12 | | 4+7x=2x+9+5x | | 9=n÷5 | | k+8.5/5.9+15=-2.6 | | 10−4(3−2y)=8y+5 | | Y=5x+7x | | 51=3*4*x | | C-5.3=-6.4c= | | 16=–15+k | | 8+11x-1=18X | | 7x17=4+7(x-3) | | -5.3=-6.4c= | | −7+4x=5 |